Numerical simulation of the influence of structural imperfections and doping on the mechanical properties of single and multi walled Carbon Nanotubes [electronic resource] - Ali Ghavamian, 1985- (2011)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2011